2022
DOI: 10.3390/ijerph19148528
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Health-Risk Behaviors and Mental Well-Being of ASEAN University Students in COVID-19 Pandemic

Abstract: The prevalence of epidemiological health-risk behaviors and mental well-being in the COVID-19 pandemic, stratified by sociodemographic factors in Association of South East Asian Nations (ASEAN) university students, were examined in the research. Data were collected in March-June 2021 via an online survey from 15,366 university students from 17 universities in seven ASEAN countries. Analyzed data comprised results on physical activity, health-related behaviors, mental well-being, and sociodemographic informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…There is evidence to show that, 9 months after initiation of the outbreak of COVID-19, More than half of Chinese college students have depressive and anxiety symptoms ( Xiao et al, 2021 ). In contrast, a large proportion of college students consumed SSB (82.0, 95%CI, 81.4, 82.6; Rahman et al, 2022 ). This study hypothesized that there is an association between SSB consumption and psychological symptoms of Chinese college students.…”
Section: Introductionmentioning
confidence: 95%
“…There is evidence to show that, 9 months after initiation of the outbreak of COVID-19, More than half of Chinese college students have depressive and anxiety symptoms ( Xiao et al, 2021 ). In contrast, a large proportion of college students consumed SSB (82.0, 95%CI, 81.4, 82.6; Rahman et al, 2022 ). This study hypothesized that there is an association between SSB consumption and psychological symptoms of Chinese college students.…”
Section: Introductionmentioning
confidence: 95%
“…A web-based survey conducted during the early COVID-19 containment phase in France reported an increase of up to 28.4% in caloric/salty food intake [ 17 ]. Studies on university students from seven South East Asian countries had revealed that during the pandemic, over 50% of students had a high salt intake [ 49 , 50 ]. A study conducted in India involving children aged 9–14 years found that 25% of them consumed ultra-processed foods with high levels of salt during the pandemic [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cross-sectional survey among Universitas Gadjah Mada (UGM) students for 1 week in the second semester of the academic year 2020/2021 (11-17 April 2021), following the ethical principles of the Declaration of Helsinki. This study is a part of the ASEAN University Network Health Promoting Network (AUN-HPN) Physical Activity in College Students (PACS) Project (Rahman et al, 2022), which collected PA data and its correlates in UGM on three-phase ( 28…”
Section: Acknowledgmentsmentioning
confidence: 99%